2016
DOI: 10.1155/2016/2020489
|View full text |Cite
|
Sign up to set email alerts
|

Late-Developing Supernumerary Premolars: Analysis of Different Therapeutic Approaches

Abstract: This case series describes the different potential approaches to late-developing supernumerary premolars (LDSP). LDSP are supernumerary teeth (ST) formed after the eruption of the permanent dentition; usually they develop in the premolar region of the upper and lower jaw. The choice to extract or to monitor the LDSP depends on many factors and has to be carefully planned due to the several risks that either the monitoring or the extraction could provoke. These four cases of LDSP showed different treatment plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…At age 22 years, all supernumeraries reported were still present, with almost complete root formation and a chronological age of 13 to 14 years. Many other studies have also reported late-developing supernumerary teeth in the premolar region [18, 29, 32, 34, 36–38].…”
Section: Etiologymentioning
confidence: 99%
“…At age 22 years, all supernumeraries reported were still present, with almost complete root formation and a chronological age of 13 to 14 years. Many other studies have also reported late-developing supernumerary teeth in the premolar region [18, 29, 32, 34, 36–38].…”
Section: Etiologymentioning
confidence: 99%
“…However, the supernumerary crypt and early stage of mineralization can be easily overlooked due to the lingual position relative to the normal premolar roots. Moreover, supernumerary premolars may interfere with orthodontic space closure and affect the stability of ortho dontic treatment [7,10,15].…”
Section: Discussionmentioning
confidence: 99%
“…In a several reports of late-developing supernumerary teeth, they were mostly found in the mandibular premolar region [2,5,6,9,11,14,17]. Their prevalence in an orthodontic population has been reported to be 0.64% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the term "third dentition" has been proposed to describe supernumerary teeth that develop and appear after the completion of the usual configuration of 32 permanent teeth, representing a dental anomaly of number in the human species (1)(2)(3). Although this clinical phenomenon is relatively frequent in the global population (with an estimated prevalence between 1.5 and 3.8% in permanent dentition), the exact etiology of this anomaly remains unknown (2,4,5).…”
Section: Introductionmentioning
confidence: 99%